Earthquake Activities along the Sagaing Fault Zone, Central Myanmar: Implications for Fault Segmentation - Santi Pailoplee (2022)
In this study, the three terms related to the seismic activities of the Sagaing Fault Zone (SFZ), central Myanmar, of the possible maximum magnitude, return period, and probability of exceedance (POE) of an earthquake of given magnitude were evaluated and mapped using an improved earthquake catalog (free of duplicate records, foreshocks, aftershocks and recording artifacts) and implementation of a statistical approach. As a result, the SFZ was separated into five segments with different seismicity levels. The highest hazard level was found for the segment between Myitkyina-Northern Mandalay, with a likely generation of an Mw 6.4-7.2 earthquake in the next 50 years. For the Naypyidaw-Bago segment, the hazard levels were in the comparatively medium range with a magnitude 6.0-7.0 Mw earthquake return period of 20-50 and 100-200 years, respectively. The Offshore Andaman Sea segment of the SFZ was defined to have the lower hazard, with only a 10% or lower POE of a 7.0 Mw earthquake within the next 50 years. Therefore, effective mitigation plans should be prepared for this area and in particular for the region nearby to the Myitkyina-Northern Mandalay segment as the highest earthquake-prone area.